THE EFFECT OF HESA-A (NATURAL DRUG) ON VISUAL ACUITY IN AGE RELATED MACULAR DEGENERATION: A RANDOMIZED DOUBLE BLIND CONTROLLED CLINICAL TRIAL - Ahmadi, Amrollah; Ghanbari, Heshmatollah; Soheilian, Masoud; Naseri, Mohsen (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
We investigated the clinical efficacy and safety of HESA-A (a drug of herbal-marine origin) in the treatment of age related macular degeneration (AMD). In a randomized double blind clinical trial 280 eyes of 280 (157 F, 123 M) patients with wet and dry AMD were randomly assigned in treatment or placebo groups. Patients in treatment group received HESA-A tablet 25 mg/Kg twice a day orally and controls received placebo with the same method for 4 weeks. Visual acuity at baseline and after one month of treatment was measured and compared between two groups. All patients were followed up for 5 months after treatment. Mean patients’ age was 69.06Â±8.49 years. At the end of study visual acuity improved significantly from 1.69Â±0.65 LogMar to 1.03Â± 0.40 LogMar in treatment group but not in controls (P: 0.000 and P: 0.67 in treatment and control groups respectively). No drug reaction or recurrence was reported during the study and 5-month post treatment follow up period in HESA-A treated group. This study showed significant efficacy and safety of HESA-A in improvement of visual acuity in AMD patients in short term.